Other-race categorisation advantage in a binary- vs. ternary-response race categorisation task*. Issue 2 (17th February 2018) - Li, Yongna; Tse, Chi-Shing; Sun, Jianmin
ABSTRACT: When categorising a face based on race, people respond faster to other-race faces than own-race faces [Other-Race Categorisation Advantage (ORCA)]. Five experiments were conducted to examine the ORCA in Chinese participants in race categorisation tasks. Participants classified a face either as Chinese vs. non-Chinese (binary response) or as Caucasian, Indian, or Chinese (ternary response). Experiments 1A and 1B replicated the ORCA with Chinese vs. Caucasian and Chinese vs. Indian faces, respectively, in a binary-response task. Experiments 2A/2B and 3 presented faces of all three races in the ternary- and binary-response tasks. Task type was manipulated between and within participants in Experiments 2A/2B and 3, respectively. The typical ORCA occurred in the binary-response task, but did not consistently so in the ternary-response task. These results indicate that neither the race-feature hypothesis [Levin, D. T. 1996. Classifying faces by race: The structure of face categories. Journal of Experimental Psychology: Learning, Memory, and Cognition, 22 (6), 1364–1382] nor the differential processing hypothesis [Zhao, L., & Bentin, S. 2011. The role of features and configural processing in face-race classification. Vision Research, 51 (23-24), 2462–2470] could fully account for the ORCA observed in the ternary-response task.